The antiquities trade in Arica during the Peruvian Republican period (1824-1880): The role of the British community as a by-product of the informal empire - Lagos-Flores, Octavio (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2023)
The port of Arica was part of the global network of exchanges established by the North Atlantic powers in their process of global colonial expansion during the 19th century, which in Latin America sought to position them as new hegemonic forces in the region, replacing Spain. Arica was constituted as a node in this network, participating in it as a zone of commercial exchanges and intercultural contacts. One dimension of these exchanges was the trade in antiquities, mainly archaeological objects associated with pre-Hispanic cemeteries, which were intensively exploited from the beginning of the Hispanic colonial period. In this way, Arica functioned as a repository of archaeological specimens, where a diversity of agents interacted, within which the resident British community played a leading role over the local élite.
Keywords: pre-hispanic antiquities; antiquities trade; colonial expansion; informal imperialism